Incorporation of microencapsulated hydrophilic and lipophilic nutrients into foods by using ultrasound as a pre-treatment for drying: A prospective study - Rojas M.L. (2019)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project n° 2016/18052-5; to the National Council for Scientific and Technological Development (CNPq, Brazil) for the productivity grant of P.E.D. Augusto (306557/2017-7); and to FONDECYT-CONCYTEC (Peru) for the M.L. Rojas Ph.D. scholarship (grant contract number 087-2016-FONDECYT).